2022
DOI: 10.17159/2078-516x/2022/v34i1a12528
|View full text |Cite
|
Sign up to set email alerts
|

Sport during the COVID-19 bio-bubble: Wellness and opinions in South African elite football

Abstract: Background: COVID-19 imposed challenges on professional sport, with restrictions leading to the delay in the completion of the South African Premier Soccer League (PSL). Creating a biologically safe environment (BSE) provided a solution enabling the 2019/2020 season to be completed. Objectives: Evaluating the impact that the BSE had on player wellness and what coping mechanisms were used in the BSE. Methods: A questionnaire was distributed to PSL teams on the final weekend in the BSE. It consisted of three val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…[1] Research has identified that COVID-19 increased the phenomenon of mental health disorders, which was evident in an increase in mental fatigue and depression in football. [6] Ali and Green [17] found a strong correlation between DASS-21 factors, age and ethnicity; however, the present study found contradictory results.…”
Section: The Impact Of Covid-19 On the Mental Health Of Cricket Playerscontrasting
confidence: 81%
See 1 more Smart Citation
“…[1] Research has identified that COVID-19 increased the phenomenon of mental health disorders, which was evident in an increase in mental fatigue and depression in football. [6] Ali and Green [17] found a strong correlation between DASS-21 factors, age and ethnicity; however, the present study found contradictory results.…”
Section: The Impact Of Covid-19 On the Mental Health Of Cricket Playerscontrasting
confidence: 81%
“…and the inability to train normally are just some of the challenges athletes have had to endure due to the COVID-19 pandemic. [6] According to DASS-21, an increase in certain emotions, such as anxiety, can result in improved performance. [8] In addition, the importance of self-awareness and continuous mental health promotion among elite athletes is undervalued.…”
mentioning
confidence: 99%
“…Symptoms of RSA were associated with improvement in sprinting ability. The onset of COVID-19 increased the demand for play as playing schedules were compressed, potentially leading to an increase in physical and emotional weariness (Bahdur et al, 2022). Despite this, ''hardware'' (physiology and biomechanics) is the main focus of sports, while ''software'' (mental health and performance psychology) is often overlooked.…”
Section: Selected Mental Health and Performance Parametersmentioning
confidence: 99%
“…Mental health profiling is also limited making it necessary for teams to create holistic profiles that are needed to be competitive. Research has identified that COVID-19 increased the phenomenon of mental health disorders, which was evident in an increase in mental fatigue and depression in cricket (Malele & Noorbhai, 2023), football (Bahdur et al, 2022), and other sporting codes (Bansal & Sheriff, 2021; Fröhlich et al, 2021; Grobler et al, 2022). The sedentary behavior that most athletes opted for during lockdown escalated the effects of deconditioning and increase in mental illness (Farren et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 epidemic caused novel and unusual stress on a variety of social groupings, including athletic codes. [1,2] The entire schedule of sporting events for the year 2020 has been impacted by the coronavirus disease-2019 (COVID-19) pandemic. [3,4] Sports events were postponed or cancelled due to the high risk of COVID-19 transmission through close contact and droplets, and physical separation was recommended to break the chain of transmission.…”
Section: Introductionmentioning
confidence: 99%